2021
DOI: 10.1111/aogs.14156
|View full text |Cite
|
Sign up to set email alerts
|

Association between travel time to delivery unit and unplanned out‐of‐hospital birth, infant morbidity and mortality: A population‐based cohort study

Abstract: Introduction: Over the last decade, a number of delivery units have been closed in Sweden, justified by both economic incentives and patient safety issues. However, concentrating births to larger delivery units naturally increases travel time for some parturient women, which may lead to unintended negative consequences. We aimed to investigate the association between travel time to delivery unit and unplanned outof-hospital birth, and subsequent infant morbidity and mortality. Material and methods:We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The issues of travelling in labour caused stress and anxiety to many women, and they feared giving birth before they reached the hospital. Increased travel distance has shown association with risk of giving birth outside of hospital [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The issues of travelling in labour caused stress and anxiety to many women, and they feared giving birth before they reached the hospital. Increased travel distance has shown association with risk of giving birth outside of hospital [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Swedish antenatal and obstetric care is publicly funded, almost all pregnant women attend antenatal care regularly [ 12 , 13 ], and give birth in hospitals [ 14 ]. All healthcare providers in Sweden are obliged by law to report antenatal, obstetric, and neonatal data to the NBHW, where the records are merged, quality checked, and annually released for use as the MBR (Law concerning registers of health data: 1998:543, and regulation specifically about the MBR: 2001:708).…”
Section: Introductionmentioning
confidence: 99%
“…Except for historical lapses in reporting from specific hospitals, mothers who are non-residents at time of birth are sometimes temporarily assigned non-valid PINs, which impede the linking between registers. Planned or unplanned home births are rare in Sweden (estimated < 1%), [ 14 ] and although possible to report to the register, data on such births may be missing to a high degree.…”
Section: Introductionmentioning
confidence: 99%
“…This has proven to be a factor in increasing the risk of complications and mortality 6 . A Swedish study showed that if a woman's travel time to the maternity ward exceeds 30 minutes, there is a greater chance that she will deliver before arrival 9 . Research also demonstrates that unplanned out-of-institution births often take place without competent maternity care 7,10,11 , even though having a skilled birth attendant present is the most crucial factor for preventing obstetric complications 6,12 .…”
Section: Introductionmentioning
confidence: 99%